Ask Question
28 November, 06:30

How to solve 4p (q-1) + q (1-p) ?

+3
Answers (1)
  1. 28 November, 07:07
    0
    p = - q / (3 q - 4)

    Step-by-step explanation:

    Solve for p:

    4 p (q - 1) + q (1 - p) = 0

    Expand and collect in terms of p:

    q + p (3 q - 4) = 0

    Subtract q from both sides:

    p (3 q - 4) = - q

    Divide both sides by 3 q - 4:

    Answer: p = - q / (3 q - 4)
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “How to solve 4p (q-1) + q (1-p) ? ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers